Hongaarse studenten in Groningen - Bozzay, Réka (Acta Neerlandica, 2015)
The University of Groningen played en important role in the Hungarian peregrinatio academica. 290 Hungarian and Transylvanian students enrolled the university between 1627 and 1795. The frequency of visiting this university was influenced by political and economic circumstances: the persecution of Protestants in Hungary, wars, and disallowance of studying abroad caused by economic restrictions. The Groningen University took care of its citizens; it had its own court, canteen etc. According to archival sources, Hungarians were summoned to the university court a couple of times. The most frequent reason was debt to the landlord or landlady. There is also one case known when a Hungarian was expelled from the university due to a rape attempt against a local girl. Luckily, the most Hungarians behaved properly and received financial support from the university for paying their meal in the canteen, publishing their disputations, and covering the costs of their journey back home.